Unsur-Unsur Intrinsik dalam Naskah Drama Rakyat Manokwari Berjudul Yambin - Ummu Fatimah Ria Lestari (Balai Bahasa Provinsi Papua, 2019)
This research discuss about the intrinsic unsures that build the scenario was titled Yambin. This scenario had taken from the folklore of Manokwari people with the same title. This drama tells about the girl named Yambin. She lifes with her grandma named Yati. Oneday, they met with a youngman named Kopiori. She and that youngman get married. Then their family gets much problems after that. But all problem can be solved by grandma Yati’s purslane. Finally, they are happy forever.Based from analysist of this scenario, the writer has find that its intrinsic unsures consist of caracterictics, plots, dialogs, epilogs, monologs, prologs, acts, and setting.